Efficacy and Safety of Tenofovir Alafenamide (TAF) and Tenofovir Disoproxil Fumarate (TDF) Followed by TAF in Chronic Hepatitis B Patients of East Asian Ethnicity Following 5 Years of Treatment - Wong, Grace Lai‐Hung; Gane, Edward; Pan, Calvin Q.; Fung, Scott; Ma, Mang M.; Izumi, Namiki; Shalimar; Lim, Seng Gee; Chuang, Wan‐Long; Mehta, Rajiv; Lim, Young‐Suk; Yee, Leland J.; et al. (Alimentary pharmacology & therapeutics, 2025)
Tenofovir alafenamide (TAF) has shown non-inferior efficacy to tenofovir disoproxil fumarate (TDF), with superior bone and renal safety. To characterise 5-year TAF efficacy and safety in patients of East Asian ethnicity from pivotal Phase 3 studies. Patients were randomised (2:1) to receive TAF or TDF for up to 3 years of double-blind treatment, followed by open-label TAF. Patients either continued TAF or switched from TDF to TAF at Week 96 (TDF → TAF 3 years) or Week 144 (TDF → TAF 2 years) of treatment. Efficacy endpoints (virologic, biochemical and serologic) and safety were assessed. Among 591 patients of East Asian ethnicity (TAF, n = 401; TDF → TAF 3 years, n = 84; TDF → TAF 2 years, n = 106), high rates of virologic control were achieved (89%, 94% and 92%, respectively) at Year 5 (missing = failure analysis). At Year 5, rates of alanine aminotransferase normalisation (85%, 90% and 78%) and hepatitis B e antigen loss (36%, 43% and 44%) were similar. Following the switch from TDF to TAF, changes in fasting lipid parameters were consistent with removal of the known lipid-lowering effect of TDF. However, changes in the total cholesterol to high-density lipoprotein ratio (marker of cardiovascular risk) were minimal and comparable in all groups by Year 5. Renal and bone parameters improved after switching. Through 5 years, rates of virologic suppression were high in East Asian patients treated with TAF or switched from TDF to TAF. TAF and TDF were well tolerated, with improved renal and bone safety observed in patients switching from TDF to TAF.